Answer:
Z + 12
Step-by-step explanation:
Z-(-12)
Z + 12
Double negative turns into positive
Answer:
18:27:45 = 2:3:5
Step-by-step explanation:
Answer:
false
Step-by-step explanation:
If the vertical line hits more than 1 point it is not a function because the x value cannot repeat in order for it to be a function
Answer:
a) 1/27
b) 16
c) 1/8
Step-by-step explanation:
a) ![x^{-3/2}](https://tex.z-dn.net/?f=x%5E%7B-3%2F2%7D)
One of the properties of the exponents tells us that when we have a negative exponent we can express it in terms of its positive exponent by turning it into the denominator (and changing its sign), so we would have:
![x^{-3/2}=\frac{1}{x^{3/2} }](https://tex.z-dn.net/?f=x%5E%7B-3%2F2%7D%3D%5Cfrac%7B1%7D%7Bx%5E%7B3%2F2%7D%20%7D)
And now, solving for x = 9 we have:
![\frac{1}{x^{3/2}}=\frac{1}{9^{3/2} } =\frac{1}{27}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%5E%7B3%2F2%7D%7D%3D%5Cfrac%7B1%7D%7B9%5E%7B3%2F2%7D%20%7D%20%20%3D%5Cfrac%7B1%7D%7B27%7D)
b) ![y^{4/3}](https://tex.z-dn.net/?f=y%5E%7B4%2F3%7D)
This is already a positive rational exponent so we are just going to substitute the value of y = 8 into the expression
![y^{4/3}=8^{4/3}=16](https://tex.z-dn.net/?f=y%5E%7B4%2F3%7D%3D8%5E%7B4%2F3%7D%3D16)
c) ![z^{-3/4}](https://tex.z-dn.net/?f=z%5E%7B-3%2F4%7D)
Using the same property we used in a) we have:
![z^{-3/4}=\frac{1}{z^{3/4} }](https://tex.z-dn.net/?f=z%5E%7B-3%2F4%7D%3D%5Cfrac%7B1%7D%7Bz%5E%7B3%2F4%7D%20%7D)
And now, solving for z = 16 we have:
![\frac{1}{z^3/4} } =\frac{1}{16^{3/4} } =\frac{1}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bz%5E3%2F4%7D%20%7D%20%3D%5Cfrac%7B1%7D%7B16%5E%7B3%2F4%7D%20%7D%20%3D%5Cfrac%7B1%7D%7B8%7D)
This is an arithmetic series with first term a1 = 3 and common difference = 3
Sum after 365 days = (365/2)[ 2*3 + (365-1)*3]
= 200,385 pennies = $2003.85 Answer